Status of E-Commerce as Correlated to the Development of Plant Community - Cathlyn Joy N Dia; Chester Alexis C Buama; Maryjane D Fuentes; Marry Anne S Gonzales; Regina E Gloria; Noel H Natividad (Research Synergy Foundation, 2023)
During the time of the pandemic in 2020, it is notable that the trend of plants flourished. However, at present, there is a decline in demand. The Municipality of Bay, Province of Laguna, is recognized as the